Assessment of coastal flooding and wave overtopping of the tide embankment section in Tacloban City: An experimental and numerical study - Ngo, Patrick Sahun N. (Animo Repository, 2019)
The aftermath of the devastating Typhoon Haiyan in 2013 prompted the Philippine government to advocate for more resilient cities against natural disasters through the Build Back Better policy. One of the projects under this is the Road Heightening and Tide Embankment (RHTE) Project which aims to protect the coastal communities of the Leyte region against future storm surges. As the tide embankment is currently being constructed, it is important to assess its reliability against future coastal hazards. The main failure mechanism investigated was excessive overtopping which is the primary response of a coastal structure when subjected to extreme waves. This also causes coastal flooding to the protected areas. In modelling the wave-structure interaction between generated waves and the tide embankment, a 1:30 scale representative geometry of the tide embankment was tested inside a wave flume with a beach profile where the dam-break mechanism was used to generate turbulent bores that was similar to wave mechanism of the storm surge. Water level conditions in the flume served as experimental variables. As wave height was the main parameter being investigated, wave gauges were placed before, on, and after the structure. The wave height distribution was evaluated with and without the coastal structure. To validate the experimental model numerically, the exact dimensions of the wave flume rendered drawn using SolidWorks and simulated using ANSYS CFX. Using the finite volume method to solve for the continuity and momentum, the Volume of Fluid (VOF) method was used to track the free surface of the fluid flow. In actual scale, the presence of the tide embankment reduced the water level by 0.4 to above 1 m with respect to the mean sea level. The significant wave height distributions from both experimental and numerical modelling were in close agreement with one another, except that the results of ANSYS CFX overestimated the wave heights. A second design of the tide embankment was investigated in the presence of a return wall using ANSYS CFX. Comparing its significant wave height with that of the tide embankment without return wall, the reduction in wave heights after the structure ranged from 0.1 to 0.5 m. Based from the wave profiles generated from both tests, it can be concluded that scenarios worse than the storm surge produced by Typhoon Haiyan were shown since at a wave height of 6 to 8 m approaching the structure, the wave height inland is approximately 3 m above mean sea level. For the computation of overtopping discharge, the significant wave height at the toe of the structure was determined from all trials. Lastly, hazard curves were generated to establish the relationship between the significant wave height at toe of the structure and its corresponding overtopping discharge which was compared to the tolerable overtopping limits for embankment seawalls with a threshold value of 0.05 m3/s-m.